Ministro di culto e imam - Iurato, Giovanna Maria Rita (Il diritto ecclesiastico, 2022)
Minister of worship and imam · This paper deals with the role of ministers of worship in the Italian legal system. Having sketched the contours of these subjects under the law, it then moves on to consider the mechanisms of governmental approval for their appointment. Major developments concerning the dialogue between state and faith-based officials are then analysed also in light of the Italian principle of secularism. Lastly, the condition of Imams is also considered having regard to the main statutes of national Islamic organisations.